Application of Trichoderma Biopesticide on Chili Plants (Capsicum frutescens L.) Catas Variety - Azarine Sade Devitasari; S Sutarman (Demeter: Journal of Farming and Agriculture, 2025)
This study aims to determine the effect of the interaction between the application of Trichoderma solid formula biopesticide applied to the soil and through canopy spraying on the growth and health of vegetative phase cayenne pepper (Capsicum frutescens) plants. This study was conducted from September to December 2024 in Pacet, Pasinan Hamlet, Cepokolimo Village, at an altitude of 450 meters above sea level. This field study was designed as a factorial Randomized Block Design. The first factor was the application of solid biofertilizer (soil treatment), which consisted of three levels: no biofertilizer application but using complete chemical fertilizer; soil treatment at planting or starting from sowing; and soil treatment one month after planting. The second factor was the application of liquid Trichoderma biofertilizer. The observation variables were length increase (cm), leaf number increase, average time of first flowering (days), branch increase, and plant health. The interaction effect of biopesticide application through soil treatment had a significant effect on plant health with a disease symptom intensity of 9.38% compared to the control of 16.67%. The interaction effect on plant growth was not significant.